2002
DOI: 10.1590/s0102-05362002000400030
|View full text |Cite
|
Sign up to set email alerts
|

1-Methylcyclopropene delays tomato fruit ripening

Abstract: Figure 5. Total carotenoids (mg.kg -1 fresh weight) of tomato fruits treated with 1-MCP, stored for 2 days at ambient conditions (23±1°C; RH 80-85%), with subsequent storage for 15 days at 20±1°C and 85-95% RH. Vertical bars indicate ± SD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
7
16
1
2
Order By: Relevance
“…This finding is in accordance with reports of Moretti et al (2002), Wills and Ku (2002) and Mostofi et al (2003) pointing out that 1-MCP treatment delays tomato fruit ripening, including their softening. With extending storage period from 3 to 4 weeks flesh firmness showed a tendency to decrease, which indicated that ripening process in 1-MCP treated fruits was still going slowly.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in accordance with reports of Moretti et al (2002), Wills and Ku (2002) and Mostofi et al (2003) pointing out that 1-MCP treatment delays tomato fruit ripening, including their softening. With extending storage period from 3 to 4 weeks flesh firmness showed a tendency to decrease, which indicated that ripening process in 1-MCP treated fruits was still going slowly.…”
Section: Resultssupporting
confidence: 93%
“…The effect depends on 1-MCP concentration and time of the treatment. It was reported that 1-MCP reduced production of ethylene, cell respiration, restrained fruit colour changes, softening, taste and aroma degradation as well as diseases of fruits (Moretti et al, 2002;Wills and Ku, 2002;Mostofi et al, 2003). There are reports that 1-MCP treatment markedly affects also ripening of tomato fruits by inhibiting ethylene production (Opiyo and Ying, 2005;Beno-Moualem et al, 2004;Tassoni et al, 2006;Watkins, 2006;Tadesse et al, 2012), significantly reduces respiration rates in the fruits (Guillén et al, 2007), delays change of fruits colour and reduces softening and decay of stored fruits (Guillén et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1A). As a kind of food preservative, n PG has a similar efficacy on fruit ripening as 1‐MCP in previous studies (Moretti et al . 2002; Sisler 2006).…”
Section: Discussionsupporting
confidence: 58%
“…In non-climacteric fruit no effect is to be expected, but in climacteric fruit the results were not uniform. For example, in mature green apricot (Prunus armeniaca) fruit, which is climacteric, 1-MCP had no effect on the increase of the concentrations of phytoene, phytofluene and b-carotene (Marty et al, 2005) while 1-MCP prevented the increase in lycopene and b-carotene concentrations in the climacteric papaya fruit (Carica papaya; Fabi et al, 2007) and total carotenoids in the climacteric tomato (Moretti et al, 2002) and dragon fruit (Selenicereus megalanthus; Deaquiz et al, 2014). 1-MCP applied before ripening also inhibited the increased expression of genes involved in carotenoid synthesis, for example in nectarine (Ziliotto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%